Kajian Kinerja Usaha Pelayanan Jasa Alat dan Mesin Pertanian (UPJA) : Kontribusi dalam Strategi Pengembangan Alat dan Mesin Pertanian (Studi Kasus UPJA di DIJ) - M. Rizki Yogatama; Sunarto Ciptohadijoyo (agriTECH, 2001)
The objective of this study was to predict profit level of UPJA. It was also to discover technical and non-technical factors and understand a social-economical effect of the uPJA toward increasing farmer income and use of agricultural machinery and equipment. The sample was 28 KSO-patterned of UPJA, and farmer as user of UPJA. Data was obtained by distributing questioner, conducting direct interview with respondent and refering relevant literature. The data determined description of UPJA management in the DIJ and then it was analyzed through technically, economically, and socially approached. Technical analysis indicated that tractor capacity was high, while thresher and RMU were low. Economical analysis indicated that tractor and thresher were in not economical, because the NPV was less than 0 and BCR was less than 1. Whereas on RMU there were two samples, that can achieve NPV more than 0, and BCR more than 1. Social analysis indicated that actually farmers received and needed the presence of the technology, although the appreciation on agricultural machinery and equipment service was still low. As a whole, UPJA activity had not been good and given benefit. It needed agricultural explanation more intensive to the farmer on importance of agrocultural mechanization. It also needed to raise fee so the operating loss could be decreased.